Analisis Survei Kepuasan Mahasiswa terhadap Sistem Absensi Akademik (SIAKAD) - Syarifuddin Syarifuddin; Nor Anisa (Universitas Methodist Indonesia, 2025)
The Academic Attendance System (SIAKAD) is a crucial component in educational management at universities, aimed at facilitating the management of student attendance. This study aims to analyze student satisfaction with SIAKAD, focusing on user interface, available features, and its impact on the learning process. Data were collected through a survey involving 200 students from various programs and semesters, using a questionnaire designed to evaluate students' perceptions of the system. The results indicate that 75% of respondents access SIAKAD daily, with most spending 5-15 minutes each time. A majority of students (70%) find the user interface easy to use, although 30% of respondents indicated a need for improvements in navigation. The attendance and grade report features are the most frequently used, accessed by 85% and 70% of students, respectively. The impact of SIAKAD on the learning process is also significant, with 80% of respondents feeling that the system helps them manage attendance and enhance academic responsibility. This research is expected to provide useful insights for SIAKAD administrators in improving and developing the system in the future, as well as contribute to the literature on user satisfaction in higher education contexts. The findings also open opportunities for further studies on technology implementation in education and its effects on students' learning experiences.